ICT DEVELOPMENT AND EXPORT VOLUME IN UZBEKISTAN: REGIONAL PANEL DATA ANALYSIS (2015–2024) - Sadriddinov Ulugbek Jaloliddin ugli, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article quantitatively studies the impact of the Information and Communication Technology (ICT) Development Index (IDI) on export volume based on panel data for 15 administrative-territorial units of Uzbekistan for 2015–2024. The annual export volume of the regions (in million US dollars, log) was taken as the dependent variable, and the IDI index calculated based on the ITU methodology was selected as the main independent variable. GDP (in US dollars, log), investment volume (log), urbanization level, and trade openness indicators were included as control variables. Four models were used, including random effects (RE), fixed effects (FE), and their robustness versions. A total of 150 observations were analyzed. The results showed that the IDI index had a statistically significant positive effect only in the fixed effects model (β=1.513, p